Physiological and behavioral changes in women during the menstrual cycle and the impact of nutritional supplementation (Research, Society and Development, 2021)
The intestinal microbiota has become an important subject of study for the learning and treatment of certain pathologies. There is a huge range of symptoms associated with the menstrual cycle, from milder to more expressive symptoms. The main project of the present study was to assess the impact of nutritional supplementation during the menstrual cycle, as well as questions about physiological and behavioral changes in this phase through an integrative literature review on the subject. Scientific articles published in the last twelve years, whose studies were carried out in humans and animals, were researched and examined. After reviewing the literature, it became evident that the human microbiota has an impact on health, demonstrating that the adoption of healthy habits may be able to reduce physical and emotional symptoms during the menstrual cycle and that nutritional therapy has an essential role in the treatment. Furthermore, it is inferred to emphasize the need for individualized interventions, as emotional symptoms and dietary changes during this period vary from person to person.